2021
DOI: 10.26599/bdma.2020.9020018
|View full text |Cite
|
Sign up to set email alerts
|

IoT-based data logger for weather monitoring using arduino-based wireless sensor networks with remote graphical application and alerts

Abstract: In recent years, the monitoring systems play significant roles in our life. So, in this paper, we propose an automatic weather monitoring system that allows having dynamic and real-time climate data of a given area. The proposed system is based on the internet of things technology and embedded system. The system also includes electronic devices, sensors, and wireless technology. The main objective of this system is sensing the climate parameters, such as temperature, humidity, and existence of some gases, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(54 citation statements)
references
References 17 publications
0
53
0
1
Order By: Relevance
“…In assessing disaster resilience in different areas, (Sasaki et al, 2020) satellite imagery provides feedback on risks that can even be revealed over time (Joshi et al, 2019). Satellitebased results can be supported by on-site special (Lambrinos, 2019) and meteorological (Mabrouki et al, 2021) sensor data, and flood protection of valuable agricultural areas can also be planned with flood models (Avand et al, 2021).…”
Section: The Importance Of the System Of Systems Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In assessing disaster resilience in different areas, (Sasaki et al, 2020) satellite imagery provides feedback on risks that can even be revealed over time (Joshi et al, 2019). Satellitebased results can be supported by on-site special (Lambrinos, 2019) and meteorological (Mabrouki et al, 2021) sensor data, and flood protection of valuable agricultural areas can also be planned with flood models (Avand et al, 2021).…”
Section: The Importance Of the System Of Systems Approachmentioning
confidence: 99%
“…The data of the Internet of Things sensors (Mabrouki et al, 2021) allow the conclusions drawn from the satellite images to be verified (Majidi et al, 2021), as a measuring station (Jimenez et al, 2019) increases the number of observations, thus better downscaling solutions (Wang Q. et al, 2020) can be made. It can be used for causal exploration of plant morphological damage (Fenu and Malloci, 2019) and supports agricultural irrigation water demand planning (Ismail et al, 2020), but can also be imported into flood models (Avand et al, 2021).…”
Section: The Importance Of the System Of Systems Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, with the intervention of the IoT, various environmental parameters such as temperature, humidity, pressure, chemical pollutants, etc., can be measured remotely with precise instruments and sensors in terms of chemical and physical quantities. Sensors record values ​​and transmit them as electronic signals, and specialized intelligent and human systems make decisions based on this information [ 36 ].…”
Section: Organization Of the Iot Applicationsmentioning
confidence: 99%
“…Technically, Achieve the balance between privacy protection and system service performance. Even so, the existing research has many differences in the core security cognition and key functions of the platform, especially in data-driven applications, the trade-off between data availability and privacy, and traditional security technologies are difficult to meet the needs of platform dynamic operation [41,42]. Based on this, it is necessary to improve the security monitoring capabilities of the platform, crack the situation of resource utilization, and organize the formation of a platform security technical framework.…”
Section: Cybersecuritymentioning
confidence: 99%